Study of adsorption isotherms of green coconut pulp - Lavoyer, Fábia Carolina Gonçalves [UNESP]; Gabas, Ana Lúcia; Oliveira, Wanderley Pereira; Telis-Romero, Javier [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2013)
O Brasil é considerado um dos maiores produtores e consumidores de frutas tropicais. O coco verde (Cocos nucifera L.) se destaca tanto em termos de produção e consumo quanto em quantidade de resíduos gerada por indústrias de água de coco e pelo consumo in natura. Portanto, existe uma necessidade de aproveitamento deste subproduto. Este trabalho teve por objetivo estudar as isotermas de adsorção da polpa de coco verde e determinação do calor isostérico de sorção. As isotermas de adsorção para as temperaturas de 30, 40, 50, 60 e 70 °C foram analisadas e evidenciaram curvas do tipo III, típicas de alimentos ricos em açúcares. Os dados experimentais de umidade de equilíbrio foram correlacionados por modelos da literatura. O modelo de GAB apresentou melhor concordância com os dados experimentais, entre os modelos avaliados. O calor isostérico de sorção é considerado um indicativo de forças atrativas intermoleculares entre os sítios de sorção de vapor de água, consequentemente, um importante fator para predizer a vida de prateleira de produtos desidratados.

Brazil is considered one of the largest producers and consumers of tropical fruits. Green coconut (Cocos nucifera L.) stands out not only for its production and consumption, but also for the high amount of waste produced by coconut water industry and in natura consumption. Therefore, there is a need for utilization of this by-product. This study aims to study the adsorption isotherms of green coconut pulp and determine its isosteric heat of sorption. The adsorption isotherms at temperatures of 30, 40, 50, 60, and 70 °C were analyzed, and they exhibit type III behavior, typical of sugar rich foods. The experimental results of equilibrium moisture content were correlated by models present in the literature. The Guggenheim, Anderson and de Boer (GAB) model proved particularly good overall agreement with the experimental data. The heat of sorption determined from the adsorption isotherms increased with the decrease in moisture content. The heat of sorption is considered as indicative of intermolecular attractive forces between the sorption sites and water vapor, which is an important factor to predict the shelf life of dried products.
Estudo das isotermas de adsorção da polpa de coco verde
Keywords: subprodutos agroindustriais; coco verde; propriedades termodinâmicas; isotermas de sorção; agro-industrial by-products; green coconut; Thermodynamic properties; Sorption isotherm